THER-16. EFFICACY OF UPFRONT IMMUNE CHECKPOINT INHIBITORS IN LUNG CANCER BRAIN METASTASIS. (12th August 2019) - Barnett, Addison; Lauko, Adam; Ali, Assad; Li, Hong; Sagar, Soumya; Chao, Samuel; Pennell, Nathan; Peereboom, David; Stevens, Glen; Angelov, Lilyana; Yu, Jennifer; Murphy, Erin; et al.
Abstract: INTRODUCTION: Immune checkpoint inhibitors (ICI) have resulted in improved outcomes in a subset of patients with lung cancer. However, data describing the efficacy of ICI in lung cancer brain metastasis (LCBM) is limited. We analyzed overall survival (OS) in patients with LCBM treated with upfront ICI, defined as having received ICI within 90 days of LCBM diagnosis, compared to non-ICI therapies. METHODS: We reviewed 665 patients with LCBM who were diagnosed between 2000 and 2018 at a major tertiary care institution. Of those patients, 240 received ICI, 164 of which received ICI after 90 days and 76 received ICI within 90 days. Propensity score (PS) was calculated using a logistic regression model including age, KPS, number of baseline brain lesions, and presence of extra-cranial metastasis (ECM) at the time of BM diagnosis. OS from BM diagnosis between PS matched cohorts were compared using Kaplan-Meier, the Log-Rank test, and Cox proportional hazards model. RESULTS: Prior to PS matching, median survival between ICI and non-ICI cohorts was not significantly different (10.9 months for both, p=0.81), although more ICI patients had ECM (57.1% vs 40.9%, p=0.006). Following PS matching, the ICI (n=76) and non-ICI (n=76) cohorts had a median age (62.4 vs 62.3 years), KPS (80 for both), lesion number (2 for both), and ECM (56.6% for both). Of matched patients, 94% received SRS, 52% received WBRT, and 29% underwent surgical resection. Compared to non-ICI, the ICI cohort has a 2-year OS hazard ratio, HR=0.87 (95% CI=0.58–1.31, p=0.51). Median and 1-year survival were not significantly different between ICI and non-ICI cohorts (median: 10.9 vs 9.1 months; 1-yr: 43.0% vs 42.4%). CONCLUSION: Patients with BM from primary lung cancer who received ICI within 90 days of their BM diagnosis did not have improvement in OS compared to patients who received non-ICI therapies.